2024
DOI: 10.1038/s41598-023-50714-z
|View full text |Cite
|
Sign up to set email alerts
|

Potassium humate and cobalt enhance peanut tolerance to water stress through regulation of proline, antioxidants, and maintenance of nutrient homeostasis

Ayman M. S. Elshamly,
Zubair Ahmad Parrey,
Abdel-Rhman Z. Gaafar
et al.

Abstract: Water stress is an important factor that substantially impacts crop production. As a result, there is a need for various strategies that can mitigate these negative effects. One such strategy is the application of potassium humate (Kh) and cobalt (Co), which have been reported to enhance the resistance of crop plants. Therefore, the present experiment was designed to investigate whether the application of Kh and Co could positively affect proline, chlorophyll and mineral elements contents, and antioxidant defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
1
0
0
Order By: Relevance
“…Previous studies have also reported that foliar application of Zn affects yield and agronomic traits, enhancing the number of pods per plant Banks 84 . These results align with studies that suggest Co and Zn applications can enhance plant biomass, enzymatic actions, and physiological and chemical processes, leading to improved transpiration rates 85 , 86 . Therefore, applying the combined applications of Co + Znfol improved plant performance, growth, and nutrient uptake.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have also reported that foliar application of Zn affects yield and agronomic traits, enhancing the number of pods per plant Banks 84 . These results align with studies that suggest Co and Zn applications can enhance plant biomass, enzymatic actions, and physiological and chemical processes, leading to improved transpiration rates 85 , 86 . Therefore, applying the combined applications of Co + Znfol improved plant performance, growth, and nutrient uptake.…”
Section: Discussionsupporting
confidence: 89%